Sobres perspectives - La sobriété à l’assaut du droit - Valentin Baudouin (VertigO)
To ensure that the ecological transition becomes a reality and does not remain at the stage of incantatory discourse, a framework for action must be devised for an effective transformation of society. Sobriety, or sufficiency in English, are some of the conceptual tools that can contribute to this. Defined as an expression of temperance, in opposition to intemperance, or of measure against excess, sufficiency is a virtue of limitation which refers to the foundations of law understood as the set of rules for regulating the behaviors in society. Today, the lexical field of sufficiency is growing in French law and it is important to pay attention to the rise of legislative provisions to curb the immoderation and excesses that are at the root of the ecological crisis. By gathering various texts relating to the objective of prudent and rational use of natural resources and by relying on the injunction for the legislator to change the current trajectory, it would be possible to identify an objective of sufficiency. That is to say, the use of natural resources through the action of parsimonious, temporal and spatial moderation while respecting the principle of ecological solidarity.